2008
DOI: 10.1017/s1047951108003405
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of the index of left ventricular mass during the acute and subacute phase of Kawasaki disease, and its association with indexes of diastolic function

Abstract: Our aim was to determine whether the index of left ventricular mass increases during the acute and subacute phase of Kawasaki disease, and to investigate any relationship between this index and clinical and echocardiographic variables. We performed, therefore, a retrospective study of 66 children with Kawasaki disease, having a mean age of 2.85 years, comparing the findings with those obtained from 57 normal controls, having a mean age of 2.99 years. The data from the patients used for comparison was obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 14 publications
2
15
0
Order By: Relevance
“…Spatial myocardial electrical heterogeneity has been well described in arrhythmogenic conditions with abnormal QTd [2]. It is likely that anomalous QTd after KD could be the result of myocardial inflammation [35,41], similar to what is observed in other immune-induced myocarditis [39], but further investigation is necessary to verify that hypothesis.…”
Section: Discussionmentioning
confidence: 81%
“…Spatial myocardial electrical heterogeneity has been well described in arrhythmogenic conditions with abnormal QTd [2]. It is likely that anomalous QTd after KD could be the result of myocardial inflammation [35,41], similar to what is observed in other immune-induced myocarditis [39], but further investigation is necessary to verify that hypothesis.…”
Section: Discussionmentioning
confidence: 81%
“…Additional diagnostically helpful findings are inflammation at the Bacille Calmette-Guérin inoculation site32), anterior uveitis10,18), elevated levels of brain natriuretic peptide (BNP)33-36) and N-terminal pro-BNP37), hyponatremia22), elevation of the left ventricular mass38), and diastolic dysfunction of the left ventricle35,39). The diagnostic validities of these clinical, laboratory, and echocardiographic findings should also be tested in the future.…”
Section: Guidelines For the Diagnosis Of Incomplete Kawasaki Diseasementioning
confidence: 99%
“…We previously showed that serum albumin concentration and left ventricular mass index were significantly associated during the acute phase of Kawasaki disease, which suggests that increases in left ventricular mass index may result from myocardial swelling caused by increased vascular permeability17). Increases in left ventricular mass have been significantly associated with diastolic dysfunctions17). Thus, our findings that log-BNP was significantly associated with serum albumin concentration and left ventricular mass index, indicate a causative association between increases in left ventricular mass caused by myocardial swelling and myocardial systolic/diastolic dysfunction that induces secretion of BNP from the myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…Increased vascular permeability from vasculitis and resultant vascular leakage are key features of the pathophysiology of Kawasaki disease, and increased vascular leakage may cause hypoalbuminemia and tissue edema15). We previously showed that serum albumin concentration and left ventricular mass index were significantly associated during the acute phase of Kawasaki disease, which suggests that increases in left ventricular mass index may result from myocardial swelling caused by increased vascular permeability17). Increases in left ventricular mass have been significantly associated with diastolic dysfunctions17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation